The date of Mark's Gospel : insight from the law in earliest Christianity - Crossley, James G. (Journal for the study of the New Testament. Supplement series ;, 2004)
This book argues that MarkGÇÖs gospel was not written as late as c. 65GÇô75 CE, but dates from sometime between the late 30s and early 40s CE. It challenges the use of the external evidence (such as Irenaeus and Clement of Alexandria) often used for dating Mark, relying instead on internal evidence from the gospel itself. James Crossley also questions the view that Mark 13 reflects the Jewish war, arguing that there are other plausible historical settings. Crossley argues that MarkGÇÖs gospel takes for granted that Jesus fully observed biblical law and that Mark could only make such an assumpti.